Construction Research Congress 2009 2009
DOI: 10.1061/41020(339)114
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for Water Mains Using Fuzzy Approach

Abstract: The concept of responding to the risk of water pipelines failure has been undergoing through a great change from being active to being proactive to failure events by planning for rehabilitation plans that maintain the water main in good working conditions. This paper designs a framework to evaluate the risk of water main failure using hierarchal fuzzy expert system. There are sixteen risk-of-failure factors that represent both the probability of failure and the negative consequences of failure event and are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…After extensive literature review (e.g., Fares and Zayed 2009;Farley 2001;Farley and Trow 2003;Lambert 2001;Lambert et al 1999;May 1994) and state-of-thepractice information, a list of 22 basic factors has been identified that directly (e.g., pressure) and/or indirectly (e.g., traffic movement) influence the leakage. Based on those basic 22 leakage influencing factors and their interrelationship, a leakage potential evaluation model has been developed .…”
Section: Leakage Potential Modelmentioning
confidence: 99%
“…After extensive literature review (e.g., Fares and Zayed 2009;Farley 2001;Farley and Trow 2003;Lambert 2001;Lambert et al 1999;May 1994) and state-of-thepractice information, a list of 22 basic factors has been identified that directly (e.g., pressure) and/or indirectly (e.g., traffic movement) influence the leakage. Based on those basic 22 leakage influencing factors and their interrelationship, a leakage potential evaluation model has been developed .…”
Section: Leakage Potential Modelmentioning
confidence: 99%